Extraction of valuable metals from low-grade nickeliferous laterite ore by reduction roasting-ammonia leaching method - Chen, Sheng-li; Guo, Xue-yi; Shi, Wen-tang; Li, Dong (Journal of Central South University of Technology. Science & technology of mining and metallurgy, 2010)
Nickel and cobalt were extracted from low-grade nickeliferous laterite ore using a reduction roasting-ammonia leaching method. The reduction roasting-ammonia leaching experimental tests were chiefly introduced, by which fine coal was used as a reductant. The results show that the optimum process conditions are confirmed as follows: in reduction roasting process, the mass fraction of reductant in the ore is 10%, roasting time is 120 min, roasting temperature is 1 023–1 073 K; in ammonia leaching process, the liquid-to-solid ratio is 4:1(mL/g), leaching temperature is 313 K, leaching time is 120 min, and concentration ratio of NH 3 to CO 2 is 90 g/L:60 g/L. Under the optimum conditions, leaching efficiencies of nickel and cobalt are 86.25% and 60.84%, respectively. Therefore, nickel and cobalt can be effectively reclaimed, and the leaching agent can be also recycled at room temperature and normal pressure.